A REVIEW ON ANTIPYRETICS AND THE SYNTHESIS ON THE OXEPINE DERIVATIVES - Nurul Kasyfita (PROSIDING SEMINAR KIMIA, 2015)
A review on antipyretics and the synthesis on the oxepine derivatives has been done. This research was aimed as the early review on the antipyretics and to synthesis the oxepine derivatives from salicylic acid and benzylchloride based on the retrosynthesis approach. This research was supervised by Dr. K.M Lokanatha Rai, M.Sc in the University of Mysore.This research was done by two methods, first is the review based on the proposed functional group which will be potential for the antipyretics substance. Second, is based on the retrosynthesis approach in order to obtain the proposed product through the condensation reaction between salycilic acid and the benzylchloride with the THF solvents stirred of 48 hours formed the oxepine which was then transformed to oxime derivatives and confirmed by the IR spectrums. The proposed product was the oxepine derivatives.The review on the antipyretics showing that the potential functional group to be the antipyretics are: the salicyl alchol nitrogen derivatives; some pyrazolone and amino pyrimidine; benzopyranone derivatives; and aspirin eugenol esters. For this review, the investigated functional groups are still further to be discussed.The result of this research on the synthesis of oxepine derivatives shown that the optimum condition of the reaction between salicylic acid and benzyl chloride is at room temperature with the composition of 4 gram of salicylic acid and 4 ml of benzyl chloride was stirred in THF solvent and KOH for 48 hours. The yield of the product is 1.08 g with the confirmed spectrum of IR are: 3369 cm-1 (-OH); 1659.4 cm-1 (C=N); 1554.92 cm-1 (aromatic); 1088.3 cm-1 (N-O); 1019.83 cm-1 (C-O). It is confirmed as an oxime which is the oxepine derivatives.